Staff Guidance Note on Macroprudential Policy : Considerations for Low Income Countries. (Policy Papers; Policy Paper, 2014)
This note explores how characteristics of financial systems commonly observed in low income countries may shape the approach to the staff's advice on macroprudential policy. It explores the implications of the ongoing process of financial and institutional development for the conduct of macroprudential policy in these countries. This note is a supplement to the Staff Guidance Note on Macroprudential Policy.